اشغال صوفیاء میں سیرت سے استفادہ: Benefiting from the seerah in the Spiritual Practices of the Sufis - Hassnain Ali (Seerat Studies, 2025)
ABSTRACT: The role of Sufi scholars in the intellectual and spiritual development of Islam holds pivotal significance. Through practices such as dhikr (remembrance of God), worship, mujahada (striving against the self), riyadat discipline seclusion meditation and companionship of the righteous, the Sufis sought purification of the soul and reformation of the heart. These spiritual engagements not only contributed to the moral and inner development of individuals but also exerted profound influence on the collection ethical and intellectual structure of the Muslim community. The efforts of the Sufis were not confined to personal mystical experiences; rather they were firmly rooted in the primary sources of Islam, namely the Qur’an, the tradition of the Prophet the Prophetic biography search and established juristic principles. In this regard, Sufism emerges as a comprehensive spiritual and moral system that maintains full harmony with the Shariah. The present study analytically examines the ways in which the Sufis drew upon these fundamental Islamic sources and integrated their spiritual practices into a coherent framework that provided enduring ethical and intellectual to the Muslim Ummah.